An Intensive Diabetes Screening and Treatment Program Improves Diagnosis, Treatment and Outcomes of Diabetes in Patients Admitted with Cardiac Diseases - Su, X.-F.; Sun, L.; Liu, B.-L.; Tao, X.-J.; Li, H.-Q.; Li, F.-F.; Ye, L.; Lee, K.-O.; Ma, J.-H.; Chen, S.-L. (Experimental and Clinical Endocrinology & Diabetes, 2017)
Aim: Patients with cardiac diseases, especially ischemic heart disease, are known to have a high prevalence of diabetes mellitus (DM). They are at risk of having inadequate glucose control. An intensive diabetes screening and treatment program was developed to identify and treat DM in patients admitted with cardiac diseases.Methods: Adult inpatients of 2 cardiac wards, namely Ward-A and Ward-B, at Nanjing Hospital, Nanjing, China, were studied. Patients were randomly assigned into either ward. In addition to routine examination and treatment, an intensive screening and treatment program to identify and treat patients with DM or impaired glucose regulation (IGR) was only applied in Ward-A patients. The glycated serum protein concentration, the length of hospitalization, and medical and total hospital cost were compared between the 2 wards.Results: The prevalence of DM was 17.85% in Ward-B. With implementation of this program, DM was higher in Ward-A (29.7%) and the prevalence of IRG was 7.8%. The overall prevalence of abnormal glucose metabolism was 37.5% in Ward-A. This program is associated with significantly reduced medical cost and length of inhospital days in patients requiring percutaneous coronary intervention (PCI) and reduced both the medical and total hospital costs in patients without PCI of Ward-A as compared with those of Ward-B who received standard treatment.Conclusion: The intensive screening and treatment program increases diagnosis rate of DM and IRG in inpatient with cardiac diseases, more effectively controls hyperglycemia, and is associated with shorter length of inhospital days and lower medical and total hospital costs.The trial registry number: ChiCTR-IPR-15007487
Keywords: cardiology; health care costs; diagnosis; OGTT; adult diabetes